Interactions of xanthate molecule with different mineral surfaces: A comparative study of Fe, Pb and Zn sulfide and oxide minerals with coordination chemistry. (1st December 2020) - Weiyong, Cui; Jianhua, Chen; Yuqiong, Li; Ye, Chen; Cuihua, Zhao
Graphical abstract: Highlights: Remarkable d-p back-bonding is found in the pyrite adsorption configuration. Ionic polarization plays an important role in the galena and cerussite structures. Chemical adsorption cannot occur on sphalerite or smithsonite surfaces. Abstract: Why are xanthates widely used in sulfide minerals flotation but seldom used in oxidized ore? Herein, the principle of coordination chemistry is introduced to study the interactions of methyl xanthate with sulfide (pyrite, galena and sphalerite) and oxide minerals (hematite, cerussite and smithsonite) under weak acidic and neutral conditions. The findings show that xanthate can strongly combine with the low-spin Fe atom of the pyrite surface, and the adsorption on the galena and cerussite surfaces is attributed to the strong ionic polarization induced by the center deviations between their Pb and S atoms. However, the adsorption configurations on both the sphalerite and smithsonite surfaces are rather weak due to the highly stable Zn 3d orbital. Further analysis shows that the orbital symmetry of the methyl xanthate molecule matches well with the pyrite, galena and cerussite. Moreover, very strong hybridization occurs in the pyrite, galena and cerussite configurations, but is rarely observed in other configurations. In addition, a remarkable d-p back-bonding is found in the pyrite adsorption configuration.